Biorational management of key pests of jasmine(jasminum sambac) - Hemalatha G (Department of Agricultural Entomology, College of Horticulture, 2009)
Jasmine is cultivated extensively in South India. It is seriously damaged by numerous pests and diseases. The use of selective, biorational approaches in place of broad spectrum conventional insecticides offer several advantages in IPM programme. The present study on “Biorational management of key pests of Jasmine (Jasminum sambac)” was carried out in the Department of Agricultural Entomology, College of Horticulture, Vellanikkara. The main objectives of the study were to assess the population dynamics of key pests of jasmine and to evaluate the efficacy of biopesticides like Beauveria bassiana, Metarrhizium anisopliae, Bacillus thuringiensis, NSKE and Econeem plus along with standard insecticides such as imidacloprid, acephate, fipronil and carbosulfan. To assess the population dynamics of key pests of jasmine a survey was conducted in the farmer’s field in four locations of Thrissur district. It was found that budworm and blossom midge infestation were increased from November to March and the population of thrips and whiteflies were more during February to April, the peak flowering period. Correlation analysis of jasmine pests with weather parameters viz., maximum temperature, minimum temperature, relative humidity and rainfall revealed that a significant negative relationship exist between the relative humidity and blossom midge infestation. Flower thrips population was negatively correlated with rainfall. From the field experiment it was observed that application of B. thuringiensis at 0.1 per cent was the most effective treatment against jasmine budworm, Hendecasis duplifascialis followed by B. bassiana @1x107spores ml-1 and the rotational treatment of B. thuringiensis (0.1%) and carbosulfan (0.05%). Blossom midge infestation was significantly reduced in azadirachtin (1%) treated plants followed by NSKE (5%) sprayed plants. In the case of flower thrips and leaf thrips the rotational treatment of acephate (0.1%), imidacloprid (0.01%) and azadirachtin (1%) was found to be the most effective. For controlling the whitefly population also, the same treatment gave consistently good results. The highest yield (3405 kg ha-1) with a net profit of Rs. 3,40,500 was obtained from the plants treated with rotational application of acephate, imidacloprid and azadirachtin. But the highest benefit: cost ratio of 2.60:1 was obtained from the plants treated with B. bassiana @1x107spores ml-1 followed by M. anisopliae @1x107spores ml-1 (2.57:1).